2020
DOI: 10.1007/s11661-020-06012-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electropulsing Treatment on Microstructure and Properties of Cemented Carbide (WC-15Co)

Abstract: Electropulsing treatment (EPT) is a promising postprocessing method to optimize microstructure. In the present work, the EPT was applied to treat cemented carbide (WC-15Co). The electropulse-induced microstructural evolution in WC-15Co was investigated. Compared with the untreated sample, the transverse rupture strength and electrical resistance of the treated sample were reduced. However, there was no significant change in the scanning electron microscopy (SEM) microstructure. Therefore, electron backscatter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…One candidate method is electropulsing, which has been demonstrated to control defect density in metals and alloys. [25][26][27] We extend the concept to the semiconductor devices, recognizing that the channels and vicinity can be annealed by the effect of the electron wind force (EWF). Our recent study 28) demonstrated the rejuvenation of Ti/4H-SiC Schottky barrier diodes using high density current pulses.…”
mentioning
confidence: 99%
“…One candidate method is electropulsing, which has been demonstrated to control defect density in metals and alloys. [25][26][27] We extend the concept to the semiconductor devices, recognizing that the channels and vicinity can be annealed by the effect of the electron wind force (EWF). Our recent study 28) demonstrated the rejuvenation of Ti/4H-SiC Schottky barrier diodes using high density current pulses.…”
mentioning
confidence: 99%